PAIN CONTROL IN CONSERVATIVE DENTISTRY AND ENDODONTICS. A NARRATIVE REVIEW. - Farhan Jassam Alshammary (Chelonian Research Foundation, 2022)
Any healthcare professional who wishes to better manage pain must have an understanding of it. There are numerous potential causes of dental discomfort, each of which can present itself in a unique fashion. Acquiring a proper diagnosis constitutes the initial course of action in managing dental discomfort. Questionnaires and rating instruments, including the Visual Analog Scale, are utilized to assess pain. After receiving a diagnosis, a multitude of pain management strategies may be implemented individually or in conjunction. All pain-relieving methods will be ineffective until the root cause of the discomfort is identified and treated. Dental discomfort may be alleviated through the implementation of diverse pharmacological and non-pharmacological approaches. A diminished pain threshold may be present in patients with dental anxiety; this should be addressed through behavioral treatment. It has also been discovered that administering premedication prior to anesthetic administration improves pain management. Analgesics such as nonsteroidal anti-inflammatory drugs [NSAIDs], aspirin, and select opioids like morphine constitute the fundamental components of pain management. Anaesthetics, which may be administered subcutaneously or intravenously, represent an additional frequently employed method. Dental phobia in children can be treated with analgesics or conscious sedation, both of which are frequently employed. It has been demonstrated that audio-analgesia, hypnosis, and acupuncture are all effective pain treatments. Recently, lasers have been examined as a potential treatment for pain. It has also been demonstrated that virtual reality is an effective distraction tool. Pain can also be effectively managed through the utilization of a range of established home remedies. Consequently, it is essential to acknowledge that pain management is a complex undertaking. Keywords: Pain Management, analgesics, dental pain, anaesthetics